Polyaniline stabilized activated carbon from Eichhornia Crassipes: Potential charge storage material from bio-waste - Verma C.J.; Kumar A.; Pal S.; Sinha S.; Singh A.K.; Jaiswal A.; Prakash R. (My University, 2025)
The present work is focused on the development of a highly capacitive electrode material based on polyaniline (PAni) modified activated carbon. High porous activated carbon was prepared from aquatic weed-Eichhornia Crassipes under variation of pyrolysis temperatures, viz. 600, 700 and 800 °C (denoted as ECC 600, ECC 700 and ECC 800, respectively). Among all, ECC 800 exhibits best performance towards capacitive application. As-synthesized ECC 800 is further treated with acid to improve processability and used with an optimal amount of polyaniline to improve charge conductivity. It is observed that the ECC 800 has specific capacitance ∼293 Fg-1 at current density 0.78 Ag-1 which becomes 569 Fg-1 for oxygenated ECC 800. Further improvement in capacitance is observed for polyaniline modified activated carbon ∼1542 Fg-1 with above 88% retention of capacitance over 1000 CV cycles. Our work gives a new source of an electroactive carbon material which is cheap, eco-friendly, sustainable and shows enormous potential for charge storage application. © 2020 Elsevier Ltd